1995
DOI: 10.1113/jphysiol.1995.sp020705
|View full text |Cite
|
Sign up to set email alerts
|

Selective depression of medium‐latency leg and foot muscle responses to stretch by an alpha 2‐agonist in humans.

Abstract: 1. In standing humans, toe-up rotation of a platform induces a short-latency (SLR) and a medium-latency response (MLR) in both soleus (Sol) and flexor digitorum brevis (FDB) muscles. Toe-down rotation evokes a MLR in the tibialis anterior (TA). The SLR is the counterpart of the monosynaptic stretch reflex, but the origin of the MLR is still debated. By means of tizanidine (an a2 -adrenergic receptor agonist) we tested the hypothesis that the MLR is relayed by group II afferent fibres, since animal data indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 18 publications
2
61
0
Order By: Relevance
“…This might be related to the higher sensitivity of spinal group II inputs to neuromodulation by monoamines (midbrain structures relaying motor cortex outflow). Indeed, excitatory spinal group II inputs at cervical and lumbar levels have been particularly depressed by ␣ 2 -noradrenergic agonists, while group I inputs were unchanged (Corna et al 1995;Lourenço et al 2006;Marque et al 2004;Maupas et al 2004;Rémy-Néris et al 2003). Therefore, while group I and group II commissural interneurons can receive common descending inputs, it appears that the two subpopulations can be controlled differentially rather than being coactivated during voluntary movement, as suggested in cats (Jankowska et al 2005).…”
Section: Modulation During Motor Tasksmentioning
confidence: 99%
“…This might be related to the higher sensitivity of spinal group II inputs to neuromodulation by monoamines (midbrain structures relaying motor cortex outflow). Indeed, excitatory spinal group II inputs at cervical and lumbar levels have been particularly depressed by ␣ 2 -noradrenergic agonists, while group I inputs were unchanged (Corna et al 1995;Lourenço et al 2006;Marque et al 2004;Maupas et al 2004;Rémy-Néris et al 2003). Therefore, while group I and group II commissural interneurons can receive common descending inputs, it appears that the two subpopulations can be controlled differentially rather than being coactivated during voluntary movement, as suggested in cats (Jankowska et al 2005).…”
Section: Modulation During Motor Tasksmentioning
confidence: 99%
“…The red arrow indicates the location of the stimulation. applied to the Achilles' tendon using a vibratory stimulus of 70 Hz frequency and 1 mm amplitude; (2) frequency-dependent depression of proprioceptive reflexes was tested by delivering two successive pulses of EES at intervals of 50 and 100 ms ; and (3) pharmacological modulation of EES-evoked motor responses was tested using the ␣2-adrenergic receptor agonist Tizanidine (1 mg/kg), which decreases excitability of spinal interneurons supplied by Group II fibers (Corna et al, 1995), and the sodium channel blocker tetrodotoxin (TTX; concentration, 1 M; volume of bolus, 50 l), which suppresses synaptic transmission (Tresch and Kiehn, 2000). Both pharmacological agents were injected into the subarachnoid space of the spinal cord through an inlet cannula.…”
Section: Methodsmentioning
confidence: 99%
“…Tizanidine, an α 2 adrenergic receptor agonist, selectively blocks transmission from group II afferents in the lumbar spinal cord both in the cat (Bras et al 1990) and in human subjects (Corna et al 1995;Marque et al 2005). Assuming that it would have similar actions on circuits of the cervical cord, the effects of ulnar nerve stimulation on the ongoing FCR EMG activity were investigated before and after oral intake of tizanidine.…”
Section: Group Datamentioning
confidence: 99%
“…Only recently has it become possible to investigate group II pathways in the lower limb of human subjects. Most of the group II effects described so far are superimposed on group I effects, so that special tests are required to differentiate their contributions: cooling the nerve (Matthews, 1989;Schieppati & Nardone, 1997;Simonetta-Moreau et al 1999) and depression of group II excitation by tizanidine, an α 2 adrenergic receptor agonist (Corna et al 1995;Marque et al 2005). These investigations have shown that group II excitation of motoneurones, whether homonymous or heteronymous (Simonetta-Moreau et al 1999;Marque et al 2005), is more potent than excitation by Ia afferents in corresponding pathways.…”
mentioning
confidence: 99%